Aprendizagem cooperativa no contexto da sala de aula: a análise da evolução psicogenética da língua escrita de aluno com deficiência intelectual - Silva, Camila Barreto (2016)
This thesis aimed to analyze the Cooperative Learning constitutes psychogenetic evolution factor of the written language of students with intellectual disabilities in the context of common classroom. Examined whether there were differences in the evolution of syllabic writing among students with intellectual disabilities who participated in the sessions of Cooperative Learning and those in the control group. Also investigated these subjects had proactive behavior during production sessions written in the context of cooperation in the common room. Our study had a qualitative approach, using as a theoretical and methodological basis of the structural organization of the Cooperative Learning supported by Johnson, Johnson (1991, 1997, 1999). The thesis is the theoretical foundation sociointeractionist assumptions of Vygotsky, especially as the importance of interaction and the concept of mediation for learning group students; studies on the written language of psychogenesis countersigned by Ferreiro and Teberosky; and conceptions of the cognitive functioning of people with intellectual disabilities. Participated in the study six subjects with intellectual disabilities, four composing the experimental group and two control groups. ubjects attended three public schools in Fortaleza, in the 2nd and 3rd years of elementary school, and the Educational Service Specialist. The development of the research included nine procedures, including the application of pre-tests and writing post-tests, and performing 35 text production group sessions with each subject of the experimental group, a total of 140 sessions. The data revealed that, in general, subjects in the experimental group developed social skills to deal with and overcome the adversities of social-affective nature existing throughout the sessions and to position themselves in groups as the protagonist of his writing. The results showed that the subjects who participated in the sessions in groups showed behaviors of cooperative learning proposed the meeting, promoting, above all, the emergence of proactive attitudes during the construction of the collective texts, so that these subjects reflect on the system writing. Pre- and post-tests revealed changes of conceptual levels in the written language of the four subjects in the experimental group, and conceptual regressions in writing levels of the subjects in the control group. The data indicate that the cooperative learning constituted a structural approach applicable in the common room with intellectual disabilities with subjects in order to promote the development of psychogenic four study participants. The experience provided an opportunity also to subjects moments of reflection group on the writing system, making inferences and seeking autonomously solutions to your doubts and questions, an aspect that certainly contributes to the evolution of these subjects.